The Rise of Right-wing Populism and Foreign Aid in Electoral Democracies: The Case of US Trump - Hamdy, Ahmed (AUC Knowledge Fountain, 2023)
Populism has always been controversial in academia despite being undertheorized. The 21st century has witnessed a global trend of the rise of right-wing populism in electoral democracies that led to major consequences including regional disintegration as the case with Brexit in Europe and rising anti-multilateralism in the United States under the Trump administration. Whereas academic literature attempted to scrutinize correlation between the rise of populism and its effect on foreign policy, the literature on populism and foreign aid is quite scarce. This study aims to appraise the rise of right-wing populism on foreign aid in electoral democracies, focusing on the United States under Trump as the main case study due to its unique political sophistication and potential impact on the global order that makes it a sui generis case. The findings empirically show how Trump’s populist attitudes and anti-multilateral discourse have an effect on contracted foreign aid in the United States during his presidential terms.